Boost DC-DC Converter with Switched-Capacitor and Four-State Switching Cell - Dias, Julio Cesar; Lazzarin , Telles Brunelli (Eletrônica de Potência, 2024)
The integration of switched-capacitor voltage multiplier cells in basic converter topologies has been studied to provide voltage gain and voltage stress reduction. However, SC cells do not provide current sharing and additionally they induce high current spikes in the devices, which are limitations of these structures to operate in high power levels. The main contribution of this paper is to overcome this drawback proposing the use of a multistate switching-cell for current sharing in SC-based boost converters, which reduces the current stress in the power devices and increases the power levels of this family of converters. The proposed concept can be generalized for m number of SC cells and n number of switching cells to increase the voltage gain and current levels. Furthermore, it can be applied to other basic structures. The theoretical analysis of the proposed structure was evaluated experimentally in a 3 kW boost-type dc-dc converter, achieving 200 V to 1200 V voltage gain, and reaching 98.4% of maximum efficiency.